First-Person Pronouns as Authorial Presence in Research Articles: A Cross-Linguistic Study of English and Indonesian - Tsaqifa, Tsabita Intan; Rahmasari, Shafira (Lexicon, 2025)
This paper is a corpus-based study that attempts to examine how first-person pronouns are used in English research articles in comparison to Indonesian research articles in the field of linguistics since Indonesian writers tend to avoid the use of first-person pronouns in academic writing. This study intends to identify the types of first-person pronouns used to express authorial presence in English and Indonesian research articles. It also explores the discourse functions of first-person pronouns that serve in English and Indonesian research articles. The source of the data consists of 40 research articles that are collected from reputable journals and analyzed using AntConc. This study employs the categorization of discourse functions proposed by Hyland (2002). The results show that I, my, me, we, our, us, and the author(s) are employed by the English authors and kami, penulis, and peneliti are used by the Indonesian authors. The pronoun we is the most frequently used by both English and Indonesian authors. The English authors tend to use the pronoun I rather than the Indonesian authors. The Indonesian authors hide themselves in the phrases of the author(s) and the researcher(s).  In addition, the results also identify that these first-person pronouns serve discourse functions in research articles.